Neurosurgical randomized trials in low- and middle-income countries (2020)
BACKGROUND:The setting of a randomized trial can determine whether its findings aregeneralizable and can therefore apply to different settings. The contribution of low- andmiddle-income countries (LMICs) to neurosurgical randomized trials has not been system-atically described before.OBJECTIVE:To perform a systematic analysis of design characteristics and methodology,funding source, and interventions studied between trials led by and/or conducted in high-income countries (HICs) vs LMICs.METHODS:From January 2003 to July 2016, English-language trials with>5 patientsassessing any one neurosurgical procedure against another procedure, nonsurgicaltreatment, or no treatment were retrieved from MEDLINE, Scopus, and Cochrane Library.Income classification for each country was assessed using the World Bank Atlas method.RESULTS:A total of 73.3% of the 397 studies that met inclusion criteria were led by HICs,whereas 26.7% were led by LMICs. Of the 106 LMIC-led studies, 71 were led by China. If Chinais excluded, only 8.8% were led by LMICs. HIC-led trials enrolled a median of 92 patients vsa median of 65 patients in LMIC-led trials. HIC-led trials enrolled from 7.6 sites vs 1.8 sitesin LMIC-led studies. Over half of LMIC-led trials were institutionally funded (54.7%). Themajority of both HIC- and LMIC-led trials evaluated spinal neurosurgery, 68% and 71.7%,respectively.CONCLUSION:We have established that there is a substantial disparity between HICsand LMICs in the number of published neurosurgical trials. A concerted effort to investin research capacity building in LMICs is an essential step towards ensuring context- andresource-specific high-quality evidence is generated.